Implementation of UPBJJ-UT Governance Policy Innovations Based on the Indonesian National Qualifications Framework in East Nusa Tenggara Province: Strategic Collaboration Approach Perspective - Agus Joko Purwanto; Rulinawaty; Setyo Kuncoro; Jasrial (GoAcademica Research & Publishing, 2023)
Government policy in improving the quality of higher education and the quality of graduates through the Ministry of Research, Technology, and Higher Education's policies continues to experience significant development. One of the innovation policies for Higher Education governance is the realization of the Indonesian National Qualifications Framework (KKNI) which adapts to current developments in the current era of digitalization. This research seeks to see how the strategic collaboration approach is in developing the capacity of